To Study the Correlation between Acetabular Cup Size and Vertical Offset in Primary Total Hip Arthroplasty - Singh, Dr. Mohit; Pawar, Dr. Inder; Tomar, Dr. Aakash; Krishnan, Dr. Rohan; Bisht, Dr. Amit (International Journal of Innovative Research in Medical Science, 2022)
Study design: Prospective Observational study. Objectives: To study whether the acetabular cup size and vertical offset in primary total hip arthroplasty are correlated or both are independent of each other. If correlated, whether the acetabular cup size and vertical offset in primary total hip arthroplasty are directly related to each other or inversely. Methods: A prospective study was conducted in Department of Orthopaedics, PGIMSR, New Delhi. 25 cases of ages 20 to 70 years were identified who had undergone primary total hip arthroplasty for various indications were included in the study. All the patients were assessed post operatively for acetabular cup size and vertical offset using plain X-ray pelvis with bilateral hip joints- AP view the very next day of surgery and Lower limb length discrepancy was assessed. Results: There is a significant positive correlation between acetabular cup size and vertical offset in patients undergoing primary THA with a correlation coefficient of 0.893 and p-value < 0.001.Conclusion: Accurate size and correct positioning of implant is essential in THA for restoration of normal biomechanics of hip joint and correction of LLD thereby providing a good functional outcome to the patient and there is a significant positive correlation between acetabular cup size and vertical offset in patients undergoing THR.